Risk factor profile and extubation outcomes in critically ill patients. A single-center prospective observational study - Abdul Waheed Mir; Shafat A Mir; Falak Ara; Rashid Fazli; Sahu Mushtaq; M Akbar Shah; Khalid Sofi (Asian Journal of Medical Sciences, 2024)
Background: The problem of extubation failure (EF) remains unexplored in low-resource settings, where predicting the extubation outcomes are more challenging. Aims and Objectives: This study investigates the incidence of EF and its predictors among patients who received mechanical ventilation (MV) in a tertiary care intensive care unit (ICU). Materials and Methods: This is a prospective observational study of 130 patients ≥18 years of age receiving MV for ≥48 h and tolerating spontaneous breathing trials in the ICU of a low-resource setting. We collected data on the baseline characteristics and clinical profiles. Patients were categorized into EF and extubation success (ES) groups. Multivariate logistic regression analyses were performed to identify independent predictors for EF. A p value of <0.05 is considered statistically significant. Results: We included 130 patients, and 43 (35.3%) had developed EF. The identified predictors for EF: Moderate to copious secretions (adjusted odds ratio [AOR]: 3.426 [95% confidence interval [CI] 1.281–10.82]), age >60 years of age ([AOR]: 4.135 [95% CI 1.294–11.93]), and prolonged duration of MV ≥10 days ([AOR]: 4.571 [95% CI 1.392–15.33]). Conclusion: Moderate to copious secretions, patients >60 years of age, and prolonged duration of MV ≥10 days were the best predictors of EF.